Can idiosyncratic drug reactions occur in quick succession? a case of cross sensitivity between levetiracetam and phenytoin - Nayak, Chitralekha Anilkumar; Kakode, Kalyani Pai; Rataboli, Padmanabh V. (International Journal of Basic & Clinical Pharmacology, 2017)
The occurrence of adverse drug reactions (ADRs) to more than one drug in quick succession can cause diagnostic dilemma to the doctor and increased burden of suffering to the patient. We present a single case report of a 23 year old female who developed rash and agranulocytosis in quick succession as ADRs to phenytoin and levetiracetam respectively. These antiepileptic drugs (AEDs) were prescribed as prophylaxis against post traumatic seizures (PTS). Hence a proper rationale for the prophylactic treatment of PTS and pharmacovigilance for early detection of adverse drug reactions is the need of the hour.